How far can we explain the social class differential in respiratory function? A cross-sectional population study of 21,991 men and women from EPIC-Norfolk. - McFadden, E; Luben, R; Wareham, N; Bingham, S; Khaw, K (2009)
The objective of this study is to investigate the association between occupational social class and respiratory function, as measured by forced expiratory volume in one-second (FEV(1)). We examined the cross sectional relationship between lung function and social class in a population study of 21,991 men and women aged 39-79 years living in the general community in Norfolk, United Kingdom, recruited using general practice age-sex registers in 1993-1997. There was a significant socioeconomic gradient in age adjusted lung function with a difference of 0.37 in mean FEV(1) in men and 0.20 in women, respectively between social class I and V. The age adjusted OR for having poor lung function was 4.13 (95% CI 2.66-6.42) in men and 2.64 (95% CI 1.74-3.99) in women for social class V compared to I. This difference was substantially attenuated after adjustment for height, weight, smoking status, respiratory illness, educational level, living in a deprived area, physical activity and plasma vitamin C levels. There was a strong socioeconomic gradient in respiratory function. In men the gradient appeared to be largely explained by smoking status and height; in women a large part of the gradient was explained by potentially modifiable factors. This suggests that socioeconomic inequalities in respiratory function may be preventable or modifiable and highlights factors for further exploration.